1970
DOI: 10.3329/ptcb.v16i1.1106
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Shoot Formation in Eggplant (<i>Solanum melongena</i> L.)

Abstract: Among the in vitro derived different explants such as cotyledonary leaf, hypocotyl, shoot tip and root of two local varieties, namely Singhnath and Kazla (BARI Begun-4) of eggplant (Solanum melongena L.) cotyledonary leaf was found to be the best for multiple shoot regeneration. High frequency direct organogenesis of shoots was achieved from cotyledonary leaf in MS supplemented with 1.0 mg/l BAP and 1.0 mg/l Kn. Anatomical studies using freezing microtome supported the formation of shoots through organogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
30
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 15 publications
8
30
1
Order By: Relevance
“…IBA is widely used PGR for root induction (Mir et al, 2008;Rahman et al, 2006), although several authors demonstrated rooting in PGR-free medium during organogenesis (Sarker et al, 2006;Taha, Tijan, 2002). In the present study, a good rooting response was established in both tested media: hormone-free and medium supplemented with IBA (Table 4.).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…IBA is widely used PGR for root induction (Mir et al, 2008;Rahman et al, 2006), although several authors demonstrated rooting in PGR-free medium during organogenesis (Sarker et al, 2006;Taha, Tijan, 2002). In the present study, a good rooting response was established in both tested media: hormone-free and medium supplemented with IBA (Table 4.).…”
Section: Discussionsupporting
confidence: 60%
“…Higher number of roots was induced on MSR0. Similar results for rooting in PGRs-free medium have been reported in S. melongena (Sarker et al, 2006;Taha, Tijan, 2002). The potential of in vitro regenerated plantlets to be used for in vivo establishment was investigated with plantlets transferred to pots under culture-room conditions (Figure 1f.).…”
Section: Msc -Ms Callus Mediumsupporting
confidence: 56%
“…Eggplants are common and popular vegetable crops grown in the subtropics and tropics (Sarker et al, 2006). They are perennial but grown commercially as an annual crop.…”
mentioning
confidence: 99%
“…Anatomically and histolosically, longitudinal sections of leaf explants formed numerous meristematic zones within the tissue, that subsequently converted into shoot buds (Mukherjee et al, 1991). The formation of shoot buds was characterized Bhat et al, 2013 Hypocotyl (inverted) MS + 0.5 mgL -1 TDZ Mallaya and Ravishankar, 2013 by the appearance of shoot apex with the developing leaf primordial (Sarker et al, 2006). Genotype played important role in organogenesis of the shoots directly from the explants.…”
Section: Organogenesismentioning
confidence: 99%